Bacterial diversity and community structure of salt pans from Goa, India - Gawas, Priti; Kerkar, Savita (Frontiers in Microbiology, 2023)
In Goa, salt production from the local salt pans is an age-old practice. These salt pans harbor a rich diversity of halophilic microbes with immense biotechnological applications, as they tolerate extremely harsh conditions.Detecting the existence of these microbes by a metabarcoding approach could be a primary step to harness their potential. Three salt pans viz. Agarwado, Curca, and Nerul adjoining prominent estuaries of Goa were selected based on their unique geographical locations. The sediments of these salt pans were examined for their bacterial community and function by 16S rRNA amplicon-sequencing. These salt pans were hypersaline (400 -450 PSU) and alkaline (pH 7.6 -8.25), with 0.036 -0.081 mg/L nitrite, 0.0031-0.016 mg/L nitrate, 6.66-15.81 mg/L sulfate, and 20.8-25.6 mg/L sulfide. The relative abundance revealed that the Pseudomonadota was dominant in salt pans of Nerul (13.9 %), Curca (19.6 %), and Agarwado (32.4 %). The predominant genera in Nerul, Curca, and Agarwado salt pan sediments were Rhodopirellula (1.12 %), Sulfurivermis (1.28 %), and Psychrobacter (25.5 %) respectively. The highest alpha diversity (Shannon-diversity Index) was observed in the Nerul salt pan (4.8) followed by Curca (4.3) and Agarwado (2.03). Beta diversity indicated the highest dissimilarity between Agarwado and the other two salt pans (0.73) viz. Nerul and Curca and the lowest dissimilarity was observed between Nerul and Curca salt pans (0.48). Additionally, in the Agarwado salt pan, 125 unique genera were detected, while in Nerul 119, and in Curca 28 distinct genera were noted. The presence of these exclusive microorganisms in a specific salt pan and its absence in the others indicate that the adjacent estuaries play a critical role in determining salt pan bacterial diversity. Further, the functional prediction of bacterial communities indicated the predominance of stress adaptation genes involved in osmotic balance, membrane modification, and DNA repair mechanisms. This is the first study to report the bacterial community structure and its functional genes in these three salt pans using Next-Generation Sequencing. The data generated could be used as a reference by other researchers across the world for bioprospecting these organisms for novel compounds having biotechnological and biomedical potential.